1986
DOI: 10.3382/ps.0650337
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Calcium on Bone Calcium Utilization

Abstract: In Experiment 1, 10 microCi 45Ca/day were administered to 125 hens for 10 days. Hens were then allocated to five treatments with calcium levels ranging from .08 to 3.75% of the diet. In Experiment 2, hens with morning oviposition times were randomly allocated to 11 treatments that were periods of time postoviposition ranging from 6 hr to 24 hr, in 2-hr increments (Experiment 2). At the end of each 2-hr period, eggs from 25 hens were removed from the uterus. The 18-, 20-, and 22-hr treatments were replicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 10 publications
0
14
1
Order By: Relevance
“…The mechanism of this effect is probably connected with the possibility that the slower solubility of large-particle limestone (grit) and its prolonged retention time in the gizzard also makes Ca available at night, when there is no feed intake by hens but when the shell calcification process is occurring intensively (Roland and Harms, 1973). This would prevent the mobilisation of bone Ca and P reserves, a process which could affect eggshell quality (Farmer et al, 1986). The results of a study by Zhang and Coon (1997) showed that large-particle limestone (> 0.8 mm) with lower in vitro solubility was retained in the gizzard for a longer time, which significantly increased in vivo solubility and could lead to improved Ca retention in layers.…”
Section: Eggshell Qualitymentioning
confidence: 99%
“…The mechanism of this effect is probably connected with the possibility that the slower solubility of large-particle limestone (grit) and its prolonged retention time in the gizzard also makes Ca available at night, when there is no feed intake by hens but when the shell calcification process is occurring intensively (Roland and Harms, 1973). This would prevent the mobilisation of bone Ca and P reserves, a process which could affect eggshell quality (Farmer et al, 1986). The results of a study by Zhang and Coon (1997) showed that large-particle limestone (> 0.8 mm) with lower in vitro solubility was retained in the gizzard for a longer time, which significantly increased in vivo solubility and could lead to improved Ca retention in layers.…”
Section: Eggshell Qualitymentioning
confidence: 99%
“…Eggshell formation normally occurs during night time, when no feed consumption occurs, emphasizing the birds dependence on intestinal and skeletal calcium (Ca) reserves for shell calcification. Scott et al (1971), Brister et al (1981) and Farmer et al (1986) suggested that the prolonged retention time of larger particles limestone in the acidic environment of the gizzard would provide more available ionic calcium (Ca 2+ ) during night-time, which could be utilized for eggshell calcification. Consequently, the maintenance of adequate Ca reserves in the gastrointestinal tract (GIT) would reduce the dependency on skeletal Ca for eggshell formation, thereby limiting the mobilization of medullary Ca reserves (Farmer et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Scott et al (1971), Brister et al (1981) and Farmer et al (1986) suggested that the prolonged retention time of larger particles limestone in the acidic environment of the gizzard would provide more available ionic calcium (Ca 2+ ) during night-time, which could be utilized for eggshell calcification. Consequently, the maintenance of adequate Ca reserves in the gastrointestinal tract (GIT) would reduce the dependency on skeletal Ca for eggshell formation, thereby limiting the mobilization of medullary Ca reserves (Farmer et al, 1986). Other authors Keshavarz & McCormick, 1991) also reported an improvement in eggshell quality and egg weight by replacing a part of ground limestone with larger particles.…”
Section: Introductionmentioning
confidence: 99%
“…Pereira (2004) reported that birds fed normal levels of calcium presented greater weight of shells than those fed lower levels, confirming the results found in this study. This effect had been known for a while because of the results found by Outerhout (1980), Farmer et al (1986) and Clunies et al (1992 a, b) which had already reported this effect of shell weight in relation to the level of calcium in the diet.…”
Section: Resultsmentioning
confidence: 91%